EFEK STIMULASI DINI MENGGUNAKAN BABY WALKER DAN BALANCE BIKE PADA PERKEMBANGAN MOTORIK ANAK - casman casman; Ita Pursitasari; Avid Wijaya; Yanis Helfiyanti (Poltekkes Kemenkes Jambi, 2021)
Background: The early stimulation of gross motor development children in Indonesia needs to be optimized, but the parent's standard choice kind of stimulation was unclear. This could be caused by the mother's lack of knowledge about the types of stimulation to choose. Mostly parents choose baby walkers in stimulating the walking phase of children, while balance bikes are unfamiliar by parents as a type of gross motor stimulation when children can walk. The purpose of this article is to provide an overview of the effects of early stimulation used a baby walker and a balance bike on a toddler's development phase. Method: This article is a scoping review. The article was searched from some databases, includes CINAHL, ScienceDirect, ProQuest, and ClinicalKey. The search used a combination of several keywords: